Improved adsorption properties of granulated copper hexacyanoferrate with multi-scale porous networks. Issue 20 (9th February 2016) - Lee, Kyoung-Moo; Kawamoto, Tohru; Minami, Kimitaka; Takahashi, Akira; Parajuli, Durga; Kido, Gentoku; Yoshino, Kazunori; Tanaka, Hisashi
Abstract : Designed porous copper hexacyanoferrate micro-capsule beads (CuHCF-MCB) were prepared using freeze-drying (FD). Abstract : Designed porous copper hexacyanoferrate micro-capsule beads (CuHCF-MCB) were prepared using freeze-drying (FD). Multi-scale porous networks composed of Angstrom, nanometer, and micrometer sizes were obtained in the desired shapes using a simple drying process. They provide special benefits such as fast kinetics and high capacity. The Cs adsorption equilibrium and kinetics fit the pseudo-second-order kinetic model well. The adsorption rate of FD-CuHCF-MCB was improved to about 15 times higher than that of the heat-drying process because of the highly multi-scale porous structure of FD-CuHCF-MCB, which facilitated solution flow and rapid ion-diffusion inside the MCB.